Recent advances in cancer research and therapy - Liu, Xin-Yuan.; Pestka, Sidney; Shi, Yu-Fang. (London ; Waltham, MA : Elsevier Science, 2012)
Cancer continues to be one of the major causes of death throughout the developed world, which has led to increased research on effective treatments. Because of this, in the past decade, rapid progress in the field of cancer treatment has been seen. Recent Advances in Cancer Research and Therapy reviews in specific details some of the most effective and promising treatments developed in research centers worldwide. While referencing advances in traditional therapies and treatments such as chemotherapy, this book also highlights advances in biotherapy including research using Interferon and Super--
Includes bibliographical references.
Keywords: Neoplasms -- Therapy; Research